Synthesis and molecular screening of 2-methyl-6,11-dihydro-5h-[1,2,4]triazolo[1',5':1,6]pirido[3,4-b]indol-5-carbonic acid and its esters - Fedotov, S. O.; Федотов, Сергій Олегович (Запорізький державний медико-фармацевтичний університет, 2025)
The aim of the study is to synthesize novel, previously undescribed indole-containing derivatives of 1,2,4-triazole, to perform molecular docking studies and to evaluate their potential for further practical application.
Keywords: тези доповідей